Recent regional agreements : why so many, so fast, so different and where are they headed? - Whalley, John (The Centre for International Governance Innovation WaterlooCA, 2006)
Attempts to document and discuss the growth of regional trade agreements. Focuses on the United States, the European Union, China, India and the agreements of other countries. Discusses the implications for the trading system